Transfer of remote ischemic preconditioning plasma from heart transplant patients into isolated perfused rat hearts prior ischemia/reperfusion injury—a translational study of cardioprotection - Bingöl, Gizem; Jesurasa, Steve; Stroethoff, Martin; Jagdfeld, Julian David; Henning, Leila Sophie; Roth, Sebastian; Lurati Buse, Giovanna; M'Pembele, René; Raupach, Annika (Frontiers in Cardiovascular Medicine, 2025)
Remote ischemic preconditioning (RIPC) has been shown in several experimental studies as an organ protective procedure against ischemic injury, but the implementation of RIPC into routine clinical practice has so far failed due to contradictory study results. However, in order to identify patient groups that could benefit from RIPC, numerous clinical trials have been initiated, but only one study with patients undergoing heart transplantation (HTX). In HTX patients, RIPC appears to be cardioprotective when used immediately before surgery, while it has not been investigated whether the cardioprotective effect of RIPC is longer lasting. Therefore, this study assessed if a RIPC procedure prior to HTX has a cardioprotective potential in a later time window. To avoid masking a potential cardioprotective effect of RIPC in HTX patients by reduced susceptibility to cardioprotective signals due to comorbidities and medications in these patients, this study investigates the protective potential of this plasma in healthy young rats. Thus, male HTX patients were treated with a sham or a RIPC procedure (3 cycles with 5 min inflating/deflating) via a blood pressure cuff at the left upper limb prior surgery. After HTX, blood was collected at arrival on intensive care unit, 24 and 48 h post-surgery. The isolated plasma was transferred to isolated-perfused rat hearts before induction of ischemia/reperfusion injury. Cardiac function was determined by left ventricular pressure measurements and infarct size by triphenyltetrazolium chloride staining. In all measurements, no differences were observed between the sham- or RIPC plasma-treated groups at the respective time points. This suggests that RIPC plasma from HTX patients, at least in the experimental setup used, has no cardioprotective potential at later time points. This lack of effect could for instance be explained by either no or an insufficient amount of cardioprotective signals are produced or/and released into the blood following the RIPC procedure and needs to be explored in future studies.